An update on COVID-19 pandemic: the epidemiology, pathogenesis, prevention and treatment strategies. Issue 7 (3rd July 2021) - Tsang, Hin Fung; Chan, Lawrence Wing Chi; Cho, William Chi Shing; Yu, Allen Chi Shing; Yim, Aldrin Kay Yuen; Chan, Amanda Kit Ching; Ng, Lawrence Po Wah; Wong, Yin Kwan Evelyn; Pei, Xiao Meng; Li, Marco Jing Woei; Wong, Sze-Chuen Cesar
ABSTRACT: Introduction: To date, the transmission of Coronavirus Disease-2019 (COVID-19) is still uncontrollable with the fact that the numbers of confirmed and death cases are still increasing. Up to 1st October 2020, 33, 842, 281 confirmed cases and 1, 010, 634 confirmed deaths have been reported to the World Health Organization from 216 different countries, areas and territories. Despite the urgent demand for effective treatment strategies, there is still no specific antiviral treatment for COVID-19 and the treatment guidelines for COVID-19 vary between countries. Area covered: In this article, we summarized the current knowledge on COVID-19 and the pandemic worldwide. Moreover, the epidemiology, pathogenesis, prevention and different treatment options will be discussed so that we shall prepare ourselves better to fight with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Expert opinion: The situation of the COVID-19 pandemic is still unpredictable. There is no effective vaccine or specific anti-viral drug to treat serve COVID-19 patients. Combination therapies have shown promising clinical improvement. Repurposing FDA-approved drugs might be one of possible treatment options. Without specific treatment and vaccines for COVID-19, the most effective way to prevent from being infected is to generate an ecosystem with effective protection, precautions and preventive measures.